Impact of Cilia Ultrastructural Examination on the Diagnosis of Primary Ciliary Dyskinesia. (September 2013) - Simoneau, Tregony; Zandieh, Stephanie O.; Rao, Devika R.; Vo, Phuong; Palm, Kara E.; McCown, Michael; Kopel, Lianne S.; Dias, Allan; Casey, Alicia; Perez-Atayde, Antonio R.; Zhong, Zhaohui; Graham, Dionne; et al.
Ultrastructural examination of cilia is the "gold standard" for diagnosing primary ciliary dyskinesia. There is little evidence suggesting the most effective method of procuring a ciliary biopsy and scant benchmark data on rates of conclusive biopsies or on the diagnostic impact of such biopsies. To critically assess rates of inconclusive, positive, and negative ciliary biopsies and to identify clinical factors associated with conclusive results, we reviewed ciliary biopsies submitted for electron microscopy from 2006 to 2011, noting whether specimens were adequate for analysis and whether the ciliary structure was normal. The biopsy site, method used, procedurist's specialty, and clinical diagnoses were determined. Biopsy findings were categorized by diagnostic impact. Over 5 years, 187 patients had 211 biopsies. Conclusive results were obtained on 133/211 biopsies (63%); the remainder were insufficient. The rate of inconclusive biopsies did not vary significantly ( P > 0.05; Fisher's exact) among sampling methods. Abnormal results were identified in 8/133 (6.0%) of the adequate specimens. Forceps compared to brush biopsies (abnormal in 4/12 versus 4/121 of the adequate specimens, P = 0.002), along with multiple biopsy samples (taken on same or different days) compared with a single biopsy sample (abnormal in 3/12 versus 1/110 of the adequate specimens, P = 0.01), were more likely to yield an abnormal result. Only 63% of pediatric ciliary biopsies provide adequate morphology for analysis, the large majority of these samples showing normal ciliary anatomy. The method of obtaining biopsies did not significantly affect result conclusiveness. Understanding the diagnostic impact of ultrastructural analysis is important as new diagnostic algorithms are developed for primary ciliary dyskinesia.